(untitled) (Global Journal of Medical Research, 2021)
The author wishes to enlarge an important current debate among obstetricians trying to sensitize specialists of obesity/endocrinology/nutrition, and make them aware of a possible very important debate: having a "normal shaped" baby (neither too small, nor too big, 10% of SGA, small for gestational age and 10% of LGA, large for gestational age), is possible by an optimal gestational weight gain (optGWG) during pregnancy. This is a simple mathematical linear equation, y= ax+b (y being optimal gestational weight gain, optGWG, x being pre-pregnancy body mass index, ppBMI). Beginning with severe obesity (36 kg/m²), women should not gain weight during their pregnancy, while they should lose weight in higher BMIs (e.g. losing 6 kg for a 40 kg/m² morbid obese). This is predictable since the first trimester of pregnancy.